2010
DOI: 10.1177/1753193409360955
|View full text |Cite
|
Sign up to set email alerts
|

Homodigital dorsal adipofascial reverse flap: anatomical study of distal perforators and key points for safe dissection

Abstract: Dorsal adipofascial flaps have been used in the surgical reconstruction of complex injuries distal to the eponychial fold. Such injuries produce nail matrix devascularization/necrosis so that nail bed reconstruction can be a challenging technical problem. Irregular scarring of the nail bed and regrowth anomalies of the nail lamina can result, with both functional and cosmetic impairment of the finger. This study aimed to define the precise vascular anatomy of the dorsal adipofascial flap that has previously be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Unlu et al used dorsal adipofascial flaps for fingertip amputation proximal to the nail matrix; they did not achieve an axial bipedicled flap because palmar digital artery is branching dorsally just proximal to the nail matrix (Unlu, Mengi, Kocer, & Sensoz, ). The vascular groundwork for the dorsal reverse adipofascial flap on the long fingers has been described in the literature (Delia et al, ; Kuyven, Fallopa, Albertoni, & Braga‐Silva, ; Oberlin, Sarcy, & Alnot, ; Strauch & de Moura, ). It is based on the distal dorsal branches of the digital arteries that originate slightly farther than the distal interphalangeal joint, on either side of the finger, forming a rich vascular bed on top of the extensor tendon, just proximal to the germinal matrix (Cormack & Lamberty, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlu et al used dorsal adipofascial flaps for fingertip amputation proximal to the nail matrix; they did not achieve an axial bipedicled flap because palmar digital artery is branching dorsally just proximal to the nail matrix (Unlu, Mengi, Kocer, & Sensoz, ). The vascular groundwork for the dorsal reverse adipofascial flap on the long fingers has been described in the literature (Delia et al, ; Kuyven, Fallopa, Albertoni, & Braga‐Silva, ; Oberlin, Sarcy, & Alnot, ; Strauch & de Moura, ). It is based on the distal dorsal branches of the digital arteries that originate slightly farther than the distal interphalangeal joint, on either side of the finger, forming a rich vascular bed on top of the extensor tendon, just proximal to the germinal matrix (Cormack & Lamberty, ).…”
Section: Discussionmentioning
confidence: 99%
“…Laulakos in his series narrowed the indications outlining the dorsal reverse adipofascial flap just for trasverse or dorsal oblique amputations that spare germinal matrix (Laoulakos et al, ). Many authors described some refinements and tips about the reverse adipofascial flap (Delia et al, ; Laoulakos et al, ; Tremolada, Abbiati, Del Bene, & Blandini, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dorsal reverse adipofascial flap might be a considerable reconstructive option [8,12,13]. Yet, the germinal matrix was sacrificed in our cases, which could inadvertently obstruct the origin of vascular supply for the dorsal reverse adipofascial flap [16]. As the safety distance for perforator preservation can be violated and compromised, the application of a dorsal reverse adipofascial flap in this circumstance should be reconsidered with extreme caution.…”
Section: Discussionmentioning
confidence: 85%
“… 8 , 9 showed that the dorsal digital artery perforator branches occur at constant and predictable intervals from the proximal interphalangeal joint, and Dellia et al. 10 showed that the arrangement of those perforators is constant extending from 5-15 mm proximal to the eponychial fold.…”
Section: Resultsmentioning
confidence: 99%